HUBUNGAN KAMPANYE PENCEGAHAN HIV AIDS TERHADAP SIKAP PADA PENDERITA HIV/AIDS (ODHA) DI PANGANDARAN (STUDI PADA PELAJAR SMA DI PANGANDARAN) - Fuady, Ikhsan; Prasanti, Ditha (Universitas Kadiri, 2019)
AbstractPangandaran is a tourist destination becomes a place that is vulnerable to the spread of HIV AIDS. HIV AIDS prevention campaign activities are very important. Various parties have carried out campaign activities to prevent the spread of HIV AIDS. The purpose of this study was to determine how the relationship between the exposure to HIV AIDS prevention campaigns with the formation of attitudes of care for people with HIV AIDS. This research was ordered by quantitative research with a survey approach. The population and sample of this research are high school students in Pangandaran. The data analysis was performed by Pearson correlation test. The results of the study note that most students or students are relatively often exposed to campaign exposure through banners, posters and whatsapps, while electronic television and radio media are relatively rare. There is a strong relationship between campaign exposure and caring attitude towards HIV AIDS sufferers. It is recommended to increase education or assistance for adolescents about preventing HIV / AIDS in direct or media campaigns in an effort to build positive attitudes and eventually will have behaviors that can avoid HIV AIDS. Besides that a positive attitude can also build awareness for people with HIV AIDS.Keywords: Campaign; HIV AIDS; AttitudeAbstrak Pangandaran sebagai kawasan destinasi wisata menjadi tempat yang rentan penyebaran HIV AIDS. Kegiatan kampanye pencegahan HIV AIDS menjadi hal yng sangat penting dilakukan. Berbagai fihak telah melakukan kegiatan kampenye penceghn penyebaran HIV AIDS. Tujuan penelitian ini adalah untuk mengetahui bagaimana hubungan antara terpaan kampanye pencegahan HIV AIDS dengan pembentukan sikap kepedulian terhadap penderita HIV AIDS. Pendelitian ini didesan dengan penelitian kuantitatif dengan pendekatan survey. Populasi dan sampel peneitian ini adalah siswa SMA di Pangandaran. Adapun analsis data dilakukan dengan uji korelasi pearson. Hasil penelitian diketahui bahwa Siswa atau pelajar sebahagian besar relatif sering terkena terpaan kampanye melalui speanduk, poster dan whatapps, sedangkan media elektronik tv dan radio relatif jarang. Adanya hubungan yang kuat antara terpaan kampanye dengan sikap peduli terhdap penderita HIV AIDS. Disarankan diperlukan peningkatan edukasi atau pendampingan bagi remaja tentang pencegahan HIV AIDS banik dalam kampanye langsung ataupun bermedia dalam upaya membangun sikap yang positif dan akhirnya akan memiliki perilaku yang dapat menghindari dari HIV AIDS. Selain itu sikap yang positif juga dapat membangun kepedulian terhadap penderita HIV AIDS.Kata Kunci: Kampanye; HIV AIDS; Sikap